Universal Low Temperature Asymptotics of the Correlation Functions of the Heisenberg Chain - Crampé, N.; Göhmann, F.; Klümper, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
We calculate the low temperature asymptotics of a function γ that generates the temperature dependence of all static correlation functions of the isotropic Heisenberg chain.